Pengaruh pendekatan kontekstual terhadap sikap ilmiah pada pembelajaran discovery peserta didik (Studi pada Materi Pokok Asam Basa) - Sugiarti Sugiarti; Halimah Husain (Seminar Nasional LP2M UNM, 2019)
. This study includes a semi-experimental research (Quasy Experiment) which aims to determine the effect of contextual approaches to scientific attitudes in the form of curiosity and academic honesty in discovery learning models of students of class XI 7 Gowa State High School. The research design used is Post-test only control group design. The sampling technique is simple random sampling, and the sample of this study is class XI MIA 1 as an experimental class and class XI MIA 3 as a control class with the number of students each class as many as 36 and 32 people. The experimental class was taught using a contextual approach to discovery learning models, while the control class was taught with a discovey model. The independent variable is the contextual approach to the experimental class and the discrete model for the control class, and the dependent variable is the scientific attitude. The results of the research data were analyzed using descriptive statistics and inferential statistics. Descriptive analysis results in both classes showed the average value of curiosity of both classes in good and sufficient categories, for academic honesty of both experimental class and successive control classes of good and less good. The results of the hypothesis testing of curiosity and academic honesty using the t- test, obtained the value of t-count = 20.15> t table = 1.99, and for academic honesty, obtained the value of t-count = 14.94> t table = 1, 99 both at a significant level, α = 0.05. Because both show the t-count value> t-table, Ho is rejected, and H1 is accepted. This shows that there is a positive influence on contextual approaches on the curiosity and academic honesty of students of class XI SMA 7 in learning acid and base.